The impact of e-commerce on the permanent establishment definition - Wepener, Suzette (Department of Private Law, 2016)
The main object of the concept of the definition of a permanent establishment in a double tax agreement is to set out the type and permanency of business activities that an entity must conduct before they can be subject to tax in another jurisdiction. Furthermore, the definition of a 'permanent establishment' as defined in article 5 of the OECD model tax convention requires the existence of a fixed place of business. This indicates the existence of a facility with a certain degree of permanence. The internet has changed the traditional international business model. It is no longer necessary that the entrepreneur, or his employees, agents, branches or intermediaries is in the country where the business is being conducted. It is clear that the internet overcomes the traditional limitations of physical presence in a jurisdiction when doing business. This poses a challenge when it comes to the determination of a 'permanent establishment', as the test is based on a physical presence of an entity in a jurisdiction. I want to determine if the current concept of a permanent establishment is still adequate to address the challenges posed by e-commerce. Taking into account that e-commerce was not a factor when the basis of the definition of the definition of a permanent establishment was formulated. The views of the OECD on e-commerce will be analysed to determine what they envisage and if they are of the opinion that the current definition is adequate to address the concept and reality of e-commerce and the taxation thereof. It is important to explore the views of the rest of the world on e-commerce and the taxation thereof. A multinational entity must be aware of the tax presence it can create in a foreign country, especially when it comes to creating a permanent establishment in that foreign country. It is my aim to identify and discuss the challenges and difficulties e-commerce poses when determining the existence of a permanent establishment and also to research certain adaptions and recommendations of the current taxing system and relevant guidelines.